Sleep and Alcohol Use Among Veterans Living With Long COVID - Rachel L. Bachrach; Caitlan A. Tighe; Nicole Beyer; Kristina Hruska; Angela Phares; Karley Atchison; Lynn Baniak; Gretchen Haas; Adam D. Bramoweth (SAGE Publishing, 2024)
Objectives: Study objectives were to: (1) better understand sleep experiences and unhealthy alcohol use among Veterans with long COVID and (2) explore providers' perceptions of barriers and facilitators to delivering evidence-based care for sleep problems and unhealthy alcohol use in patients with long COVID. Methods: VA electronic health records were used to conduct chart reviews (n = 57) of patients evaluated in a VA COVID-19 Recovery Clinic during 1 calendar year; semi-structured interviews were completed with Veterans (n = 5) and clinicians (n = 7) recruited from the clinic. Veteran participants also completed quantitative, self-report measures assessing sleep- and alcohol-related experiences and behaviors. Results: Data from chart reviews and interviews suggested that Veterans with long COVID often had pre-existing sleep problems that were exacerbated during long COVID. Patients and providers agreed that sleep interventions would be beneficial and acceptable in the COVID-19 Recovery clinic. Conversely, few Veterans with long COVID had a pre-existing alcohol use disorder (AUD) diagnosis; alcohol use occurred less frequently and was less often discussed between patients and providers. Providers had mixed viewpoints on delivering alcohol-related care in the clinic; some were highly amenable, others were unsure whether patients would be receptive. Conclusions: This study is among the first to take a mixed-method approach to understanding experiences of sleep-wake behaviors and unhealthy alcohol use in Veterans with long COVID. Characterizing sleep and alcohol-related experiences, examining associations with functioning, and exploring perspectives on treatment approaches is critical to support efforts to refine, personalize, and optimize evidence-based sleep and alcohol care for Veterans living with long COVID.